The protective effect of common fig (Ficus carica L.) leaves extract on testes of white rats (Rattus norvegicus) against paracetamol (Acetaminophen) drug. - Noori Taha Alkhafaji; Waad Sabri Shaher (Tikrit Journal of Pure Science, 2020)
Aim :This  study to investigate the protective effect of Ficus carica leaves extract against the effect of paracetamol.